Saving fish from drowning - Tan, Amy. (New York : G.P. Putnam's Sons, 2005)
On an ill-fated art expedition, eleven Americans find themselves in the Burmese jungle, where they encounter a tribe awaiting a leader and the mystical book of wisdom that will protect them from the Myanmar military regime.
Accelerated Reader AR
Keywords: Tourists -- Crimes against -- Fiction; Americans -- Burma -- Fiction; Missing persons -- Fiction; Burma -- Fiction; Suspense fiction